Effect of pulmonary recruitment maneuver and intraperitoneal bupivacaine on post-operative shoulder pain after laparoscopic cholecystectomy: A randomized comparative study - Nakhro, Sedevino; Verma, Reetu; Hemlata,; Shukla, Aparna; Gupta, Rajni (Asian Journal of Medical Sciences, 2025)
Background: Laparoscopic cholecystectomy nowadays is the preferable approach over open cholecystectomy because of early recovery and lower rate of complications. However, some undesirable effects, such as shoulder pain, which has an incidence of about 12–60% after laparoscopic cholecystectomy, can affect the early recovery of patients. Aims and Objectives: To study the efficacy of a pulmonary recruitment maneuver and intraperitoneal bupivacaine in combination for reducing shoulder pain following laparoscopic cholecystectomy. Materials and Methods: This randomized comparative study was conducted in patients undergoing elective laparoscopic cholecystectomy in a tertiary care center. A total of 46 patients were randomly assigned to two groups: group A, intraperitoneal bupivacaine instillation was done; and group B, a combination of intraperitoneal bupivacaine and a pulmonary recruitment maneuver was done. The interventions were carried out at the end of the surgery. At 1, 6, 12, 18, 24, and 48 h postoperatively, shoulder pain and abdominal were measured on a Visual Analog Scale (VAS). Results: The incidence of shoulder pain was higher in group A in comparison to group B and difference between two was statistically significant. In group A 34.78 % patients required rescue analgesia whereas in group B 13.6% patients needed rescue analgesia in postoperative period for shoulder pain. A significant difference in VAS scores for shoulder pain in the post-operative period was observed till 12 h. For abdominal pain, no significant difference in VAS scores and consumption of rescue analgesia was observed in the post-operative period. Conclusion: When intraperitoneal bupivacaine is used in conjunction with a pulmonary recruitment maneuver, shoulder pain is significantly reduced in comparison to intraperitoneal bupivacaine alone in the post-operative period after laparoscopic cholecystectomy.